Geographic Inequality in Income and Mortality in Germany - Peter Redler; Amelie Wuppermann; Joachim Winter; Hannes Schwandt; Janet Currie (Fiscal Studies, 2021)
We use data from the German Federal Statistical Office on population counts, births, deaths and income to study the development of socio-economic inequality in mortality rates from 1990 to 2015 for different age groups and both genders. Ranking the 401 German districts by average disposable income per capita, we observe large inequalities in district-level mortality rates in 1990, which had almost disappeared, or at least been flattened considerably, by 2015 particularly for infants, children and the very old. The most important driver of this reduction in inequality is German reunification in 1990. As indicated by more detailed analyses comparing districts in the former East and the former West, even five years after reunification there was a large gap in disposable income, with all Eastern districts considerably poorer than the poorest district in the West. At the same time, mortality rates were higher for all age groups and both genders in the East. Income has caught up, to the extent that there are equally poor districts in the East and West in most recent years (although the West is still much richer on average). Mortality rates in the East have improved considerably and are even below mortality rates for similarly poor districts in the West in the most recent data.
Keywords: 330; Germany; health inequality; income; inequality; mortality; SES